Evaluating high-resolution computed tomography derived 3-D joint space metrics of the metacarpophalangeal joints between rheumatoid arthritis and age- and sex-matched control participants - Tse, Justin J.; Contreras, Dani; Salat, Peter; Barber, Claire E. H.; Hazlewood, Glen S.; Barnabe, Cheryl; Penney, Chris; Ibrahem, Ahmed; Mosher, Dianne; Manske, Sarah L. (Frontiers in Medicine, 2024)
Introduction: Rheumatoid arthritis (RA) is commonly characterized by joint space narrowing. High resolution peripheral quantitative computed tomography (HR-pQCT) provides unparalleled in vivo visualization and quantification of joint space in extremity joints commonly affected by RA, such as the 2nd and 3rd metacarpophalangeal joints. However, age, sex, and obesity can also influence joint space narrowing. Thus, this study aimed to determine whether HR-pQCT joint space metrics could distinguish between RA patients and controls, and determine the effects of age, sex and body mass index (BMI) on these joint space metrics.Methods: HR-pQCT joint space metrics (volume, width, standard deviation of width, maximum / minimum width, and asymmetry) were acquired from RA patients and age-and sex-matched healthy control participants 2 nd and 3 rd MCP joints. Joint health and functionality were assessed with ultrasound (i.e. effusion and inflammation), hand function tests, and questionnaires.Results: HR-pQCT-derived 3D joint space metrics were not significantly different between RA and control groups (p > 0.05), despite significant differences in inflammation and joint function (p < 0.05). Joint space volume, mean joint space width (JSW), maximum JSW, minimum JSW were larger in males than females (p < 0.05), while maximum JSW decreased with age. No significant association between joint space metrics and BMI were found.Conclusion: HR-pQCT did not detect group level differences between RA and age-and sex-matched controls. Further research is necessary to determine whether this is due to a true lack of group level differences due to well-controlled RA, or the inability of HR-pQCT to detect a difference.